Record of Mediterranean species on island Tendra (Black See Biospheric Reserve) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
Three litoral psamophytic species of Mediterranean origin (Cerastium tauricum, Clypeola jonthlaspi, Echinophora sibthropiana) are reported for the first time on the island Tendra (Black See Biosphere Reserve). Information about the distribution of the following plants on the island (Carex liparocarpos, Medicago marina, Glaucium flavum, Alyssum borzaeanum and Elytrigia striatula), which were found earlier, are described. We hypothesize that there is a correlation between the arrival of these plants on the island and abnormally powerful storms. Finally, since all eight species are protected, we discuss the problems of preserving the populations of these plants in the region.
Keywords: Cerastium tauricum, Clypeola jonthlaspi, Echinophora sibthropiana, natural migration.